Spectroscopic And Chromatographic Approach For The Chemical Fingerprinting Of Gelsemium Elegans Via Hptlc, Lc-Ms, Ft-Ir And Nmr - Ng, Chiew Hoong (2019)
Chemical fingerprints are commonly used to perform the authentication and identification of Chinese herbal medicines (CHM). During the last few years, the fingerprint method has been developed for quality control of Chinese herbal medicines. Fingerprinting is a method that evaluates the characteristic pattern of the ingredients using one or more identification techniques. Therefore, in this study, the spectroscopic and chromatographic fingerprints of Gelsemium elegans were studied by using four analytical instruments, namely the HPTLC, LC-MS, FT-IR tri-step identification, and NMR. The purpose of this study was to compare different analytical methods on Gelsemium elegans from Fu Jian and Guang Xi province as the object of study to distinguish between the stem, leaf and root as they contained different amounts of indole alkaloid that contributes to its toxicity. The differentiation between the different parts was difficult as they came from the same species and shared similar properties and active compounds. However, the three different parts of Gelsemium elegans was successfully distinguished by the four instruments. Besides that, two abundant active compound present in Gelsemium elegans, gelsemine and koumine was qualitatively studied in HPTLC and LC-PDA-QDa. Furthermore, LC-MS/MS conditions were also developed for quantitative determination of gelsemine and koumine in Gelsemium elegans. The content of Koumine was also used to cross check the quantity in LC-MS/MS by HPTLC. Both methods showed good precision, recovery, stability and repeatability.